Challenges and Facilitators in Professional Pursuits: A Qualitative Exploration of Work Experiences in Türkiye and Perspectives of Seaborne Professionals - Özgür Sert; İbrahim Sani Mert (Journal of Eta Maritime Science)
To understand the challenges and facilitators of the business climate in Türkiye from an outsider's perspective, this qualitative and conceptual research examines foreign seaborne business professionals. The main goal is to explore the challenges and opportunities faced by male and female professionals using feedback from 37 international participants working within the Türkiye business realm. The analysis was based on a comprehensive qualitative content analysis conducted with the help of Maxqda software, which helped unveil prominent themes that define the Türkiye corporate world as expressed by the views and experiences of the respondents. This paper highlight and exposes the contrasts and similarities between expatriates' and their Turkish counterparts' experiences in seaborne business in Türkiye. Therefore, it contributes to knowledge of the operational mechanics of the Turkish business environment. The outcome of this research indicates that situational diversity, as well as flexible organizational practices, contribute significantly to creating a sustainable business environment and ensuring international business success. Türkiye's business culture offers both possibilities and problems for foreign professionals. Given these circumstances, research has established that a full-fledged global business requires sensitivity to the business culture and understanding local business practices, along with areas for improvement. This study is perceived to provide valuable perspectives for entrepreneurs who aspire to facilitate and improve the business climate in Türkiye, as well as policymakers and other administrators. In addition, it contributes to more comprehensive discussions related to Türkiye's international business environment.